7X + 5Y = - 36

X = 16 - 6Y

you have been given X, so substitute it into top equation

7(16 - 6Y) + 5Y = - 35

112 - 42Y + 5Y = - 36

112 - 37Y = - 36

- 37Y = - 148

Y = 4

------now, find X ( bottom equation )

X = 16 - 6(4)

X = 16 - 24

X = - 8

------check in both equations

7(- 8) + 5(4) = - 36

- 56 + 20 = - 36

- 36 = - 36

------top checks. Now bottom

- 8 = 16 - 6(4)

- 8 = 16 - 24

- 8 = - 8

------both check in this consistent system

X = 16 - 6Y

you have been given X, so substitute it into top equation

7(16 - 6Y) + 5Y = - 35

112 - 42Y + 5Y = - 36

112 - 37Y = - 36

- 37Y = - 148

Y = 4

------now, find X ( bottom equation )

X = 16 - 6(4)

X = 16 - 24

X = - 8

------check in both equations

7(- 8) + 5(4) = - 36

- 56 + 20 = - 36

- 36 = - 36

------top checks. Now bottom

- 8 = 16 - 6(4)

- 8 = 16 - 24

- 8 = - 8

------both check in this consistent system